Critical appraisal of interventional clinical trials assessing heated tobacco products: a systematic review - Braznell, S; Van Den Akker, A; Taylor, G; Hartmann-Boyce, J; Metcalfe, C (BMJ Publishing Group, 2022)
Objective: To critically assess the methodological characteristics and quality of interventional clinical trials investigating the effects of heated tobacco products (HTPs).